PRODUKTIVITAS PRIMER FITOPLANKTON DAN ANALISIS FISIKA KIMIA DI PERAIRAN LAUT PESISIR BARAT SUMATERA BARAT - Merina, Gusna; Zakaria, Indra Junaidi; Chairul, . (Metamorfosa: Journal of Biological Sciences, 2016)
Studies on Phytoplankton Primary Productivity and Analysis of Chemical Physics at Sea waters of the West Coast of West Sumatra has been conducted from April-October 2015 on the west coast of West Sumatra. The purpose of this study to determine the number of primary productivity generated by western sea coast of West Sumatra as well as analyze the physico-chemical conditions of the waters. The method used is the method of chlorophyll-a and Winkler methods for the measurement of oxygen and carbon dioxide as well as direct measurement by using the tool in other chemical physics parameters were observed. Primary productivity found in the coastal waters of western Sumatra on average ranged from 0.019 to 0.035 mg/ m 3 . The range of the primary productivity showed western coastal waters of West Sumatra is still relatively oligotrophic (low fertility). Physico-chemical parameters in waters off the West Coast of West Sumatra is still quite good in which all parameters were observed still under sea water quality standard.
Keywords: marine physico-chemical, phytoplankton, Padang City, Pariaman City, primary productivity